HUBUNGAN PENGGUNAAN APLIKASI WATTPAD DENGAN MINAT BACA PADA MAHASISWA BANDUNG RAYA - Karim Andike, Allifia; Prijana, Prijana; Yanto, Andri (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2024)
Wattpad is a digital reading application that is quite popular in Indonesia and is used for reading and writing, but the majority of Wattpad users are readers. Seeing the reduced interest in reading that occurs in Indonesia. This research becomes relevant when the use of the Wattpad application is linked to interest in reading considering the low interest in reading in Indonesia. The aim of this research is to determine the relationship between use of the Wattpad application and interest in reading. This research method uses a quantitative research method with the Pearson product moment correlation test using interpretation of the relationship strength table to determine the strength of the variable relationship and the rtable distribution to determine the significance between variables. The data collection technique was carried out by distributing questionnaires via social media such as Instagram, Twitter, WhatsApp, and the Wattpad reading community on Telegram. Data collection was also carried out using literature studies from previous studies on the same topic. The population of this research was UNPAD, ITB, UPI, and Tel-U students with a sample of 406 samples. The correlation test was carried out using SPSS version 23. The results of this study show that there is a significant relationship between the use of the Wattpad application and interest. With a sample size of (n)=406 and α=0.05 with a confidence level of 95%, the calculated correlation coefficient on satisfaction with using Wattpad is 0.350; intensity of Wattpad use with reading relaxation 0.209; and Wattpad reading genre preference with reading stimuli 0.516.